Yizhiqingxin Formula Alleviates Cognitive Deficits and Enhances Autophagy via mTOR Signaling Pathway Modulation in Early Onset Alzheimer's Disease Mice - Yang Yang; Zhiyong Wang; Yu Cao; Jiangang Liu; Peng Li; Hao Li; Meixia Liu (Frontiers Media S.A., 2019)
Alzheimer's disease (AD) is the most common type of dementia worldwide. The deposition of amyloid β (Aβ) is one of the most important pathological changes in AD. Autophagy, which mediates degradation of toxic proteins and maintains normal neuronal function, is dysfunctional in AD; dysfunctional autophagy is believed to be a critical pathological feature of AD. Here, we evaluated the in vitro and in vivo effects of a traditional Chinese medicinal formula called Yizhiqingxin formula (YQF) on autophagy. We determined that treatment with a high dose of YQF improved spatial memory and decreased the hippocampal Aβ burden in APP/PS1 mice, an early onset AD model. Transmission electron microscopy and immunohistochemical data revealed that YQF enhanced autophagosome formation and also increased the levels of LC3II/LC3I and Beclin1. Further, we found that YQF treatment promoted autophagic activity by inhibiting the phosphorylation of the Mammalian target of rapamycin (mTOR) at the Ser2448 site. Moreover, the level of 4EBP1 increased after YQF intervention, indicating a suppression of mTOR signaling. YQF was also found to promote autophagosome degradation, as indicated by the decreased p62 levels and increased cathepsin D and V-ATPase levels. Taken together, YQF could improve spatial learning in APP/PS1 mice and ameliorate the accumulation of Aβ while promoting autophagy via mTOR pathway modulation.